(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
The fabrication of metal parts by laser-based additive manufacturing (AM) processes is providing many applications in the medical field. The layer-by-layer growth of the component provided by powder micromelting allows, at least in theory, the incorporation of discrete sensors and wires inside the metal material. However, several process-related issues make this operation very challenging. This paper introduces the incorporation of thermal and inertial sensors inside 17-4PH steel specimens fabricated by DMLS (direct metal laser sintering) process (PCT/IB2019/053581, 02/05/2018). In the final configuration, the sensors are totally encased into the continuous metal parts with complete protection against contamination and tampering.